A Programmatic Viability Model for Planning Rural School District Organizations - Charles H. Sederberg (Journal of Research in Rural Education, 1991)
Economic, demographic, andeducationaltrends are driving aneedto restructure some rural schooldistricts. The programmatic viability model was developed to assist local educational planners determine if a district or potential combination of districts would be capable of offering state-mandated instructional and support service programs on a continuing basis. When programmed into spreadsheet software, the model analyzed the interaction ofmandatedrequirements, enrollment, andinput parametersthat includedaverage class size, average teachersalary, employee benefits, purchasedservices, andsupplyandtextbook allowances to generate numbers of sections, Full Time Equivalent (FTE) staff, and total expenditure. Revenue inputs were aggregated for comparison with estimated total expenditure. An excess of estimated revenue over expenditure indicated that a district or proposedcombination ofdistricts was programmatically viable. A pilot application ofthe model to four rural districts was used to assess utility of the model.